Difusi Modifikasi Pangan Lokal Fungsional untuk Pencegahan Penyakit Tidak Menular (PTM) - Yuniritha, Eva; Irma Eva Yani; Nur Ahmad Habibi; Safyanti; Kasmiyeti; Irfan, Delima (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service program aimed to improve public knowledge, skills, and awareness in preventing Non-Communicable Diseases (NCDs) through the utilization of functional local foods. The activity was conducted in Nagari Pasir Talang Timur, South Solok Regency, involving 46 participants, most of whom were productive-age women. The implementation methods included socialization, Focus Group Discussion (FGD), training and demonstration of functional local food processing, health screening, and evaluation through pre- and post-tests. The results showed that the majority of participants were obese (73.9%) with high-risk waist circumference (78.3%) and had cases of prehypertension to hypertension. Most participants had normal blood glucose levels (89.1%) and normal cholesterol levels (54.3%), though 41.3% were in the borderline high to high category. Nutrition knowledge scores increased from 62.5% to 86.75% after education. The program proved that nutrition education and training on functional local food processing effectively enhanced participants’ knowledge and awareness of NCD prevention. In conclusion, the diffusion of functional local foods serves as an effective community-based promotive and preventive strategy to control NCDs in rural populations.